PORTRAIT OF STUDENTS’ CRITICAL THINKING ON WORK AND ENERGY MATERIALS - Aminah; Wawan Bunawan (Journal of Learning and Technology in Physics, 2025)
This research aims to develop a critical thinking test instrument on the material of work and energy that completes the aspects of validity, reliability, level of difficulty, item discrimination, and distractor effectiveness and maps students' critical thinking skills. The type of research used is quantitative research with the Research and Development method using the Tjeerd Plomp educational design research model integrated with the ADDIE development model with 5 stages, namely analysis, design, development, implementation, and evaluation. The instrument developed consists of 20 multiple-choice questions. The test sheet consists of multiple-choice physics test items arranged based on critical thinking indicators according to Facione. The results of the content validation test, according to material, construction, and language experts, obtained an average value of 0.97 with a high validity category. The validation results using the Cohen Kappa formula obtained a Kappa value of 0.63 with a "strong" category. Data analysis using the Microsoft Excel application. The results of the small class test obtained 75% valid items, high reliability with a value of 0.82, 50% moderate difficulty level, 60% of the category item discrimination was sufficient with an average of 0.38, and 85% of the effectiveness of the good category distractor. The results of the large class test obtained 80% valid items, medium reliability with a value of 0.62, 70% of the difficulty level of the medium category, the average item discrimination of 0.32 categories was sufficient, and 95% of items with good category distractor effectiveness.. The final results of the development of Critical Thinking test instruments on Business and Energy materials at PAB 8 Saentis Private High School using the ADDIE model R&D method amounted to 16 test items with the categories of valid, moderate reliability, good differentiation, moderate difficulty level, and good distractor effectiveness. Thus, the test instruments developed in the study are said to be feasible and function to map students' critical thinking skills. Keywords: Critical Thinking; Facione; Multiple Choice; Work; Energy